Experimental Study of Influence of Plant Roots on Dynamic Characteristics of Clay - Quan Shen; Cong Tang; Chengli Zhang; Yongchun Ma (Applied Sciences)
Conducting research on the dynamic behavior of root–soil systems is crucial for accurately assessing the seismic response of ecological slopes, thereby providing a scientific foundation for the development of appropriate seismic design measures. Documentation of the improvement of soil dynamics through vegetation root systems is insufficient in the current research. This study utilizes resonance column tests to explore how root systems influence the dynamic properties of clayey soil and to uncover the mechanisms behind this enhancement. The results indicate that both root distribution and mass density have a significant impact on the soil’s dynamic shear modulus and damping ratio. When roots are distributed in the upper part of the soil, the dynamic shear modulus and damping ratio of the soil are higher than in cases of even distribution or concentration in the lower part. The dynamic shear modulus initially increases and then decreases with the increase in root mass density, reaching its peak at a root mass density of 1.5% g·cm−3. The damping ratio is influenced by both root mass density and confining pressure, with different critical root mass densities observed under varying confining pressures. The maximum enhancement in dynamic shear modulus is 27.6%, achieved at a 3% root mass density, with a peak damping ratio of 5.39%. Variations in both dynamic shear modulus and damping ratio with shear strain follow the Hardin–Drnevich hyperbolic curve.